The Role of Instrumental Emotion Regulation in the Emotions-Creativity Link: How Worries Render Individuals with High Neuroticism more Creative - LEUNG, Angela K.-Y. (Institutional Knowledge at Singapore Management University, 2014)
Based on the instrumental account of emotion regulation (Tamir, 2005), the current research seeks to offer a novel perspective to theemotions–creativity debate by investigating the instrumental value of trait-consistent emotions in creativity. We hypothesize that emotionssuch as worry (vs. happy) are trait-consistent experiences for individuals higher on trait neuroticism and experiencing these emotions can facilitate performance in a creativity task. In 3 studies, we found support for our hypothesis. First, individuals higher in neuroticism had a greater preference for recalling worrisome (vs. happy) events in anticipation of performing a creativity task (Study 1). Moreover, when induced to recall a worrisome (vs. happy) event, individuals higher in neuroticism came up with more creative design (Study 2) and more flexible uses of a brick (Study 3) when the task was a cognitively demanding one. Further, Study 3 offers preliminary support that increased intrinsic task enjoyment and motivation mediates the relationship between trait-consistent emotion regulation and creative performance. These findings offer a new perspective to the controversy concerning the emotions–creativity relationship and further demonstrate the role of instrumentalemotion regulation in the domain of creative performance.